European badger (Meles meles) responses to low‐intensity, selective culling: Using mark–recapture and relatedness data to assess social perturbation. Issue 3 (28th July 2022) - Allen, Adrian; Milne, Georgina; McCormick, Carl; Collins, Shane; O'Hagan, Maria; Skuce, Robin; Trimble, Nigel; Harwood, Roland; Menzies, Fraser; Byrne, Andrew W.
Abstract: Culling the main wildlife host of bovine tuberculosis in Great Britain (GB) and Ireland, the European badger ( Meles meles ), has been employed in both territories to reduce infections in cattle. In GB, this has been controversial, with results suggesting that culling induces disturbance to badger social structure, facilitating wider disease dissemination. Previous analyses hypothesized that even very low‐level, selective culling may cause similar deleterious effects by increasing ranging of individuals and greater mixing between social groups. To assess this hypothesis, a novel, prospective, landscape‐scale 'before‐and‐after' Test and Vaccinate or Remove (TVR) study was implemented. Test‐positive badgers were culled and test‐negative badgers were Bacillus Calmette–Guérin (BCG) vaccinated and released. Mark–recapture metrics of badger ranging and genetic metrics of social group relatedness did not change significantly over the study period. However, selective culling was associated with a localized reduction in social group relatedness in culled groups. Ecological context is important; extrapolation across territories and other disease epidemiological systems (epi‐systems) is likely to be challenging. However, we demonstrate that small‐scale, selective removal of test‐positive badgers was not associated with metrics of increased ranging but was associated with localized changes in social group relatedness. This adds to the evidence base on badger control options for policy makers. Abstract : Culling of wildlife to control spread of disease to humans and livestock can appear attractive, but culling can have counterintuitive consequences as exemplified by the bovine tuberculosis (bTB) epi‐system. Indiscriminate badger culling can result in generalised social perturbation and wider dissemination of Mycobacterium bovis, the causative agent of bTB. We used mark recapture and genetic data to demonstrate that selective culling of TB positive badgers results in no change to badger ranging and changes to social group relatedness only in groups that experienced culling.